Étude sur les populations âgées et l’accès aux soins de longue durée en français en Ontario - Belanger, Christopher; Timony, Patrick; Glaude, Normand; Bouchard, Louise (Université d'Ottawa, 2024)
Ce rapport présente une analyse de la demande et de l’offre de services de santé en français (SSF) dans le secteur des soins de longue durée (SLD) en Ontario. En nous appuyant sur des données publiques ainsi que sur des données administratives fournies par le ministère de la Santé de l’Ontario, le rapport examine : 1. la demande régionale de SSF, évaluée selon la population ontarienne âgée de 65 ans et plus et la population francophone de ce groupe d’âge ; 2. l’offre de SSF, mesurée par le nombre et le type de foyers présents dans chaque région, ainsi que par les compétences linguistiques en français de leur personnel.

Study of aging populations and access to French-language long-term care in Ontario - Belanger, Christopher; Timony, Patrick; Glaude, Normand; Bouchard, Louise (Université d'Ottawa, 2024)

Patient and Provider Satisfaction With a Geomapping Tool for Finding Community Family Physicians in Ontario, Canada: Cross-Sectional Online Survey Study. - Belanger, Christopher; Peixoto, Cayden; Francoeur, Sara; Bjerre, Lise M. (JMIR formative research, 2024)
Background: Language-concordant health care, or health care in a patient’s language of choice, is an important element of health accessibility that improves patient safety and comfort and facilitates an increased quality of care. However, prior research has found that linguistic minorities often face higher travel burdens to access language-concordant care compared to the general population. Objective: This study intended to assess patient experiences and satisfaction with an online interactive physician map that allows patients to find family physicians who speak their preferred language in and around Ottawa, Ontario, Canada, as a means of identifying areas of improvement. Methods: This study used an online survey with questions related to user satisfaction. Responses to Likert-scale questions were compiled as summary statistics and short-answer responses underwent thematic analysis. The study setting was Ottawa and Renfrew County, Ontario, and the surrounding region, including the province of Quebec. Results: A total of 93 respondents completed the survey and self-identified as living in Ontario or Quebec. Overall, 57 (61%) respondents were “very satisfied” or “somewhat satisfied” with the map, 16 (17%) were “neither satisfied nor dissatisfied,” and 20 (22%) were “very dissatisfied” or “somewhat dissatisfied.” We found no significant differences in satisfaction by preferred language, age group, physician attachment, or intended beneficiary. A total of 56 respondents provided short-answer responses to an open-ended question about map improvements. The most common specific suggestion was to show which physicians are accepting new patients (n=20). Other suggestions included data refreshes (n=6), user interface adjustments (n=23), and additional languages (n=2). Some participants also provided positive feedback (n=5) or expressed concern with their inability to find a family physician (n=5). Several comments included multiple suggestions. Conclusions: While most patients were satisfied with the online map, a significant minority expressed dissatisfaction that the map did not show which family physicians were accepting new patients. This suggests that there may be public interest in an accessible database of which family physicians in Ontario are currently accepting new patients.